2013
DOI: 10.1111/jpc.12097
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation coverage in children with cerebral palsy compared with the general population

Abstract: This study demonstrates that children with CP are at high risk of incomplete and delayed immunisation, a significant problem given the increased health-care needs of this patient group and their increased vulnerability to the complications of vaccine-preventable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
1
21
1
1
Order By: Relevance
“…We noted also that a small percentage of children with CP were either not immunised at all (1%) or did not have full immunisation uptake (16%), similar to other studies in Australia and Turkey 26 27. Further research is needed into the factors that influence uptake of full immunisation in children with CP and to identify barriers and enablers to accessing vaccination.…”
Section: Discussionsupporting
confidence: 78%
“…We noted also that a small percentage of children with CP were either not immunised at all (1%) or did not have full immunisation uptake (16%), similar to other studies in Australia and Turkey 26 27. Further research is needed into the factors that influence uptake of full immunisation in children with CP and to identify barriers and enablers to accessing vaccination.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Rance et al showed that only 15.7% of asthmatic children received flu vaccine [14]. An important delay in immunization was also observed for more than 50% of children with cerebral palsy [15] and a suboptimal coverage was reported in perinatally HIV infected children and chronic kidney diseases [16].…”
Section: Mandatory and Recommended Vaccinesmentioning
confidence: 99%
“…The indicator up-to-date vaccination is generally used to describe individuals that have received recommended vaccines by a certain age or age range, or by a specific point in time, such as school-entry. [60][61][62][63][64][65] For example, "those (children) who received all 16 doses by 19 months of age"; 65 and "received all of the vaccine doses required for school entry". 66 As noted in regard to vaccine series completion, the type, dose number, and timing of recommended/required vaccines are determined based on jurisdiction/countryspecific vaccination guidelines and thus should be specified in the report.…”
Section: Up-to-date Vaccinationmentioning
confidence: 99%
“…However, it is most commonly used to refer to receipt of specified vaccines within a very limited and specified time period following the age at which the vaccines are due. 42,58,63,65,69 Common measure of timeliness are within 30 days, 58 31 days, 65,69 4 weeks, 12 or a month 42,63 of the recommended age. If children received a recommended childhood vaccine within the specified timeframe then they were considered to have received that vaccine in a timely manner.…”
Section: Timeliness/timely Vaccinationmentioning
confidence: 99%